Bio-based Biodegradable and Biocompatible Hyperbranched Polyurethane: A Scaffold for Tissue Engineering - Das, Beauty; Chattopadhyay, Pronobesh; Mandal, Manabendra; Voit, Brigitte; Karak, Niranjan (Macromolecular Bioscience, 2013)
Hyperbranched polyurethanes are synthesized using TDI, PCL diol, butanediol, and pentaerythritol (1-5wt%) as the B4 reactant with and without the monoglyceride of sunflower oil. The biodegradation, physico-mechanical, and thermal properties are found to be tailored by varying the percentage weight of the branching unit. An MTT/hemolytic assay and subcutaneous implantation in Wistar rats followed by cytokine/ALP assay and histopathology studies confirm a better biocompatibility of HBPU with MG than without MG. HBPU supports the proliferation of dermatocytes with no toxic effect in major organs, in addition the in vitro degraded products are non-toxic. Cell adherence and proliferation endorse the bio-based HBPU as a prospective scaffold material in the niche of tissue engineering. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bio-based hyperbranched polyurethanes; Biocompatibility; Biodegradable; Cytocompatible; Tunable properties